Taxonomic names, metadata, and the Semantic Web - Page, Roderic D. M. (Biodiversity Informatics, 2006)
Life Science Identifiers (LSIDs) offer an attractive solution to the problem of globally unique identifiers for digital objects in biology. However, I suggest that in the context of taxonomic names, the most compelling benefit of adopting these identifiers comes from the metadata associated with each LSID. By using existing vocabularies wherever possible, and using a simple vocabulary for taxonomy-specific concepts we can quickly capture the essential information about a taxonomic name in the Resource Description Framework (RDF) format. This opens up the prospect of using technologies developed for the Semantic Web to add ``taxonomic intelligence" to biodiversity databases. This essay explores some of these ideas in the context of providing a taxonomic framework for the phylogenetic database TreeBASE.